2002
DOI: 10.1212/wnl.59.8.1210
|View full text |Cite
|
Sign up to set email alerts
|

Eletriptan vs sumatriptan

Abstract: Oral eletriptan (40 mg and 80 mg) is effective, safe, and tolerable in the acute treatment of migraine and yields a consistent response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
106
1
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(115 citation statements)
references
References 18 publications
6
106
1
2
Order By: Relevance
“…Eletriptan has demonstrated within-patient consistency of response based on three previous studies using a randomized, double-blind, placebo-controlled, parallelgroup design (10)(11)(12). For eletriptan 40 mg (ELE-40), consistency of response on two out of three attacks ranged from 63% to 77%, and for eletriptan 80 mg (ELE-80), two out of three consistency ranged from 72% to 82%.…”
Section: Introductionmentioning
confidence: 99%
“…Eletriptan has demonstrated within-patient consistency of response based on three previous studies using a randomized, double-blind, placebo-controlled, parallelgroup design (10)(11)(12). For eletriptan 40 mg (ELE-40), consistency of response on two out of three attacks ranged from 63% to 77%, and for eletriptan 80 mg (ELE-80), two out of three consistency ranged from 72% to 82%.…”
Section: Introductionmentioning
confidence: 99%
“…In two out of three comparative trials, eletriptan 40 mg demonstrated a significantly greater efficacy for headache and pain-free response at 2 h compared with sumatriptan 100 mg [32,33]. When headache response at 1 h was considered, eletriptan 40 mg showed a significantly higher rate compared with sumatriptan 100 mg [31,33].…”
Section: Eletriptan Versus Sumatriptanmentioning
confidence: 97%
“…The results of these trials consistently showed eletriptan's (40 and 80 mg) clinical efficacy and onset of action to be superior when compared with oral sumatriptan 100 mg. Both sumatriptan and eletriptan were well tolerated, with low incidence of adverse effects [Goadsby et al 2000;Mathew et al 2003b;Sandrini et al 2002]. Moreover, eletriptan (compared with placebo) has been demonstrated as effective in treating acute migraine in previous nonresponders, or patients not tolerant to sumatriptan [Färkkilä et al 2003].…”
Section: Eletriptan: Efficacy In Head-to-head Studiesmentioning
confidence: 99%